Sustainable Telecenters : A Guide for Government Policy - Wellenius, Bjorn (World Bank, Washington, DC, 2012)
For at least a decade, governments and non-profit organizations, often supported by bilateral aid, have experimented with tele-centers as means to extend access to computers, the Internet, and other information, and communication services to rural, and low-income urban areas of developing countries. Results have been mixed. This note proposes a guide for government policy on tele-centers conceived as private businesses - though with development functions - that are commercially sustainable beyond initial public support.